The impact of improved water access for both domestic and productive uses on human development: the case of Letsoalo-Sekororo in Limpopo Province, South Africa - Motoboli, Ma-Edward Jermina (University of Limpopo (Turfloop Campus), 2011)
The main aim of the study was to analyse the impact of improved water access for both domestic and productive uses on human development. The study was conducted in three villages in the Letsoalo-Sekororo community within the Mopani District Municipality in the Maruleng Local Municipality around the banks of the Olifants River in Limpopo Province, South Africa. The study used a total sample of 59 participants representing 40 households, 16 key informants. Three focus group discussions were held. Various variables for the households were selected and analysed using logistic regression. The method of agreement was used for key informants as well as for focus group discussions. The results from the logistic regression indicated that household size and quantity of water consumed by an individual per household was found to be showing a positive relationship to improved water access. Cattle ownership and household’s monthly income were found to be showing a negative relationship to improved water access. The results also indicated that other people’s private yard taps are the water source which showed a negative relationship to improved water access. The variable food availability throughout the year, showed a positive relationship to improved water access. Water related disease showed a negative relationship to improved water access. The results of method of agreement indicated that there are many challenges faced by the key informants. These challenges were because of the poor water reticulations and the fact that other households were unable to make their connections due to lack of a money. vii The study recommends that the Department of Water Affairs and the Maruleng Local Municipality should continue their efforts of getting enough and safe water fir the Letsoalo- Sekororo communities. Once that is done these communities will be able to get involved in income generating activities.
Thesis (M.A. (Agricultural Economics))--University of Limpopo (Turfloop Campus), 2011.
Keywords: Water access; 363.610968; Water-supply - South Africa - Limpopo; Water-supply, rural - South Africa - Limpopo